Respuesta :
Hello there!
h - 6
When h = 15
All we have to do is replace h by 15
h - 6
15 - 6
= 9
Good luck!
h - 6
When h = 15
All we have to do is replace h by 15
h - 6
15 - 6
= 9
Good luck!
evaluate h - 6 when h = 15
First write the expression:
h - 6
Plug in 15 into h in the expression (since h = 15)
15 - 6
Solve
15 - 6 = 9
your answer is 9
hope this helps
First write the expression:
h - 6
Plug in 15 into h in the expression (since h = 15)
15 - 6
Solve
15 - 6 = 9
your answer is 9
hope this helps